Development of an Effective Single-Dose PCV2/CSFV Bivalent Subunit Vaccine Against Classical Swine Fever Virus and Porcine Circovirus Type 2 - Yu-Chieh Chen; Wen-Bin Chung; Hso-Chi Chaung; Yen-Li Huang; Chi-Chih Chen; Guan-Ming Ke (Vaccines)
Background/Objectives: Porcine Circovirus Type 2 (PCV2) impairs pigs’ immune systems and increases susceptibility to co-infections, including Classical Swine Fever (CSF), a highly contagious disease listed by the World Organisation for Animal Health (WOAH) as notifiable. Therefore, swine operations in CSF-endemic regions are encouraged to immunize piglets with both PCV2 and CSFV vaccinations. Currently, there is no commercially available bivalent vaccine for PCV2/CSFV. Methods: In this study, a total of twenty 4-week-old SPF pigs were administered our formulated PCV2/CSFV bivalent subunit vaccine, containing soluble CSFV-E2 (50 µg) and PCV2-ORF2 (100 µg) antigens with a porcine-specific CpG adjuvant. After 4 weeks of vaccination, all pigs were evaluated for efficacy against PCV2 and CSFV. Results: Pigs were only immunized once and showed significantly increased neutralizing or ELISA antibody titers against both viruses four weeks post-vaccination. After viral challenges, vaccinated pigs displayed no clinical signs or lesions and had markedly reduced CSFV and PCV2 viral loads in the serum and tissues compared to controls. Conclusions: These results demonstrate that a single dose of the PCV2/CSFV bivalent subunit vaccine is safe and effective in young pigs, induces strong antibody responses, and suppresses viral replication, making it a promising tool for swine disease control and cost-effective vaccination strategies.